Abdurrauf al-Singkilis Concept of Insan Kamil in Facing The Crisis of Modern Human Morality - Ihsan, Nur Hadi; Sa’ari, Che Zarrina Binti; Hidayat, Muhammad Sofian (Islam Realitas: Journal of Islamic and Social Studies, 2022)
This paper explores Abdurrauf al-Sinkili's (1615-1693) concept of Insan Kamil in light of contemporary moral problems. The study of Insan Kamil raises human awareness about the essence of his identity as a servant of God, is crucial. It is even more so at a time when secular values and worldviews eliminate religion and God by making utilitarianism, pragmatism, materialism, and hedonism the moral foundation of humanity. Therefore, serious efforts are needed to resolve this moral quandary. The concept of Insan Kamil of Abdurrauf al-Sinkili, a vibrant Indonesian intellectual well-known in several scholarly fields, discusses the meaning, purpose, and nature of human life and can be employed as an antidote to the present crisis. This library research drew on a wide range of authoritative sources utilizing documentary techniques to collect the data and employing content analysis methods to address the issues. This paper concludes that the concept of al-Sinkili's Insan Kamil can be an antidote to today's moral dilemma, particularly regarding human attitudes that adhere to utilitarianism, materialism, pragmatism, and hedonism way of life. This finding demonstrates that the Insan Kamil concept is a viable answer to the current moral predicament. Peneleitian ini bertujuan memaparkan konsep Insan Kamil Abdurrauf al-Sinkili dalam kaitannya dengan problematika moral kontemporer. Kajian tentang Insan Kamil yang membangun kesadaran manusia tentang hakikat jati dirinya sebagai hamba Tuhan menjadi sangat penting. Terlebih lagi jika hal ini dikaitkan dengan hegemoni nilai-nilai dan worldview sekular yang mengeliminasi agama dan Tuhan karena utilitarianisme, pragmatisme, materialisme, dan hedonisme dijadikan sebagai landasan moral kemanusiaan. Oleh karena itu, diperlukan upaya yang serius untuk mengatasi dilema ini. Konsep Insan Kamil Abdurraurf al-Sinkili, seorang intelektual Indonesia yang dinamis dan kenamaan di beberapa bidang keilmuan, yang membahas tentang makna, tujuan, dan hakikat hidup manusia dapat digunakan sebagai penangkal krisis ini. Artikel ini adalah riset kepustakaan yang menggunakan teknik dokumenter untuk menghimpun data dari berbagai sumber otoritatif berupa buku, artikel, dan berbagai bahan penerbitan lainnya. Data yang terkumpul dianalisis menggunakan metode analisis konten. Penelitian ini menyimpulkan bahwa konsep Insan Kamil al-Sinkili dapat dijadikan sebagai jawaban untuk mengatasi krisis moral manusia modern dewasa ini, khususnya dalam menangani sikap manusia yang menjadikan utilitarianisme, materialisme, pragmatisme, dan hedonisme sebagai pandangan hidup. Temuan ini menunjukkan bahwa konsep Insan Kamil adalah penawar unggul bagi krisis moral manusia modern saat ini.